Effects of soil-bedrock properties on tree growth in Red Pine (Pinus brutia Ten.) natural regeneration sites under the influence of Mediterranean climate in Isparta Regional Directorate of Forestry - Yasin KARATEPE; Erdi KOYUN (Turkish Journal of Forestry, 2017)
This study was performed to determine the effect of soil-bedrock properties on growth of natural regeneration areas of Turkish red pine (Pinus brutia Ten.), which is distributes in sites with Mediterranean climate in Isparta Regional Directorate of Forestry. For this purpose, the study was conducted at 7 different site conditions within natural regeneration areas. The study was carried out with three replicates in all the areas. In these areas, the soil profiles were examined and soil samples were taken from 0-30 cm in each sample plot. Also, values of coordinates, altitudes, aspects and slopes were measured and recorded at each plot. Breast-height diameter and height of 10x3=30 trees in each sample plot were measured and recorded. Soil texture, reaction (pH), organic carbon, total nitrogen and lime analysis were performed on 21 soil subsamples, which were air-dried in the laboratory. Based on the information obtained, breast-height diameter and height of trees were interpolated according to stem analysis for the age of 10. Obtained results showed that there wasn't a negative or positive relationship between growth and soil properties. Bedrock variation has a significant impact on the growth of trees. This effect, besides the varying the position of the physiological depth of sedimentary layer and the position in rock layers as the conglomerate, was determined, it is linked to increased skeletal density of silica.